The scope of linguistic relativity in graphic and lexical numeration. (January 2021) - Chrisomalis, Stephen
Abstract: Number systems constitute one of the major domains in which language is seen as a source of variation in cognition. The notion that the features of a language's numeral system index cognitive complexity has been pervasive in anthropological linguistics since the nineteenth century. In particular, languages with small numerical vocabularies have attracted enormous interest, but other features where linguistic relativity is invoked include systemic irregularity and the presence of multiple parallel numeral systems (numeral classifiers and object-specific counting). Quite independently, the comparison of graphic numerical notations has imputed cognitive advantages, such as the idea that the Roman numerals limited mathematical progress. These discussions of linguistic relativity have been interwoven with issues of social complexity; in place of a pure language-thought relationship, the discussion has been framed through a triad of language, cognition, and social structure. To evaluate whether and how lexical numerals and numerical notations affect numerical cognition, an activity-based explanatory model is proposed in which materiality, discourse, and practice mutually constitute knowledge systems. This allows us to move past the idea that language structure has direct cognitive effects, without denying that language is relevant to numerical cognition. Highlights: Numeral systems feature widely in diverse accounts of linguistic relativity. Restricted-numeral lexicons, numeral classifiers, and irregularities are all seen as important. Both numeral words and numerical notations are regarded as having cognitive effects. The processes by which language and notation have cognitive effects are rarely explained. Numerical practices, along with language structures, explain effects on numerical cognition.